PENANDA SALAM PEMBUKA KOMUNIKASI MASSA PIDATO GUBERNUR KALBAR: TINJAUAN PRAGMATIS - Wahyu Damayanti (tuahtalino, 2018)
Greetings opening communication is a manifestation in communication that is very bound by context. The lingual unit style of the opening greeting communication is also bound by certain types of discourse. One of them is the greeting opening communication on the speech of the Governor of West Kalimantan. The purpose of this study is to describe the opening greetings of mass communication contained in the speech discourse of the Governor of West Kalimantan as a pragmatic review. The theory used in this study is about the opening greetings of mass communication by Baryadi (1989). The method used is descriptive method which not only describes existing data, but also analyzes data and summarizes it. Sources of data were obtained from literature studies of the speech of the Governor of West Kalimantan 2015 and 2017. The study data included the opening greetings used in the speech discourse of the Governor of West Kalimantan. The results of the study show six types of lingual units used as communication opening greetings, namely (1) nickname of kinship, (2) name of position, (3) name of profession, (4) name of religious title, (5) name of actor deeds, and (6) other greetings. As well as the opening greetings of interpersonal communication namely phatic phrases and phatic phrases followed by greetings.